Persuasive Key Message Factors in Marjan Syrup Advertisements from 2021 - 2024 - Kezia Maureen; Jandy Luik; Astri Yogatama (Journal of Content and Engagement, 2024)
Marketing Public Relations (MPR) emphasises not on selling (as in advertising activities) but on providing information, education, and efforts to increase understanding through the addition of knowledge about a product brand. This approach has a stronger impact, and the message conveyed is more memorable to consumers. With a more intensive and comprehensive level of communication compared to advertising, MPR represents a higher concept than regular advertising. MPR emphasises the management aspect of marketing by highlighting consumer welfare. The Marjan Syrup advertisement is one of the most unique and interesting advertisements, which certainly does not escape the attention of the Indonesian public. Since 2019, Marjan has begun to step out of its "ordinary advertisement" comfort zone by using various editing techniques while still incorporating elements of Indonesian folklore. This study provides an overview of the persuasive key message factors contained in the Marjan Syrup advertisements from 2021 to 2024. Using quantitative content analysis, this study is able to examine the message structure, message content, framing, language, and emotional appeals present in each scene of the Marjan Syrup advertisements.The results of the study indicate that the advertisements from 2021 to 2024 contain persuasive key message factors. The most prominent indicators are Message Structure and Language. Additionally, the researchers found that the persuasive key message factors in these four years are suitable for further attracting viewers to the advertisements by conveying messages that contain persuasive elements